Influence Ratio Liquidity and Operating Costs Regarding Corporate Income Tax Payable to Registered Industrial Sector Companies In Bei 2021-2025 - Lukmanul Hakim; Erliana Erliana; Ghea B Astrid Sunanto (JURNAL ECONOMINA, 2026)
Corporate income tax is one of the main sources of government revenue and is influenced by various corporate financial factors, including liquidity and operating expenses. This study aims to analyze the effect of liquidity ratios and operating expenses on corporate income tax payable in industrial sector companies listed on the Indonesia Stock Exchange (IDX) during 2021–2025. A quantitative approach was employed using secondary data obtained from the annual financial statements of 21 sample companies, resulting in 105 observations. Data were analyzed using panel data regression with E-Views 12. The results indicate that liquidity ratios do not significantly affect corporate income tax payable, while operating expenses have a significant effect. Simultaneously, liquidity ratios and operating expenses significantly influence corporate income tax payable. These findings suggest that effective operating expense management plays an important role in determining corporate tax obligations and supports more optimal financial decision-making.